2017
DOI: 10.1002/pro.3082
|View full text |Cite
|
Sign up to set email alerts
|

Mercury(II) binds to both of chymotrypsin's histidines, causing inhibition followed by irreversible denaturation/aggregation

Abstract: The toxicity of mercury is often attributed to its tight binding to cysteine thiolate anions in vital enzymes. To test our hypothesis that Hg(II) binding to histidine could be a significant factor in mercury's toxic effects, we studied the enzyme chymotrypsin, which lacks free cysteine thiols; we found that chymotrypsin is not only inhibited, but also denatured by Hg(II). We followed the aggregation of denatured enzyme by the increase in visible absorbance due to light scattering. Hg(II)-induced chymotrypsin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…However, studies have shown that cooking reduced mercury contents in mushroom by 10% and had no effect on the mercury contents in fish 45 46 47 . These studies suggest that cooking-mediated reductions in mercury content in food may be minimal, consistent with the reports that inorganic mercury and methyl mercury irreversibly bind to cellular components such as thiol-containing proteins in cells 17 48 .…”
Section: Resultssupporting
confidence: 87%
“…However, studies have shown that cooking reduced mercury contents in mushroom by 10% and had no effect on the mercury contents in fish 45 46 47 . These studies suggest that cooking-mediated reductions in mercury content in food may be minimal, consistent with the reports that inorganic mercury and methyl mercury irreversibly bind to cellular components such as thiol-containing proteins in cells 17 48 .…”
Section: Resultssupporting
confidence: 87%
“…Some hydrophobic residues such as Cys, Ala and Gly undergo much more conformational adaptations at the interface than others [ 35 ], and the two latter amino acids are particularly abundant in PL proteins. As is well-known, mercury is capable of binding cysteines [ 28 ] and histidines [ 36 ]. The binding of mercury ions to these amino acids may underlie the conformational changes we observed from the fluorescence analyses, but we cannot exclude that mercury could also be able to bind other amino acids in which PL proteins are richer, such as glycine and alanine [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that Hg binds histidines. For example, Stratton et al 2016 [ 36 ] found that Hg binds two histidines of chymotrypsin, inducing aggregation of this protein. Secondary Hg 2+ -binding sites have been suggested to also contain histidines in alpha-lactalbumin [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional Hg-binding sites cannot be excluded, likely enhancing the aggregation process, including histidine residues. In this respect, the Hg-induced chymotrypsin aggregate formation is reported to be mediated by Hg 2+ –histidine interaction [ 51 ].…”
Section: Discussionmentioning
confidence: 99%